Effect of Feeding Bypass Fat and Unprotected Oil on Feed Intake, Digestibility and Production Performance in Lactating Crossbred Cows - Shankhpal, Sachin; Gupta, R.S.; Parnerkar, S.; Dhami, A.J. (Indian Journal of Animal Nutrition, 2018)
Eighteen lactating crossbred cows (HF Ã— Jersey Ã— Kankrej) yielding 10 to 12 L of milk daily and 7-59 days in milk were divided into three groups of six animals each. The cows under T1 were fed control diet (compound concentrate mixture + dry fodder + green fodder), in T2, control diet + bypass fat supplement (200 g/h/d) and in T3, control diet + unprotected oil (170 g/h/d). There was no difference in DMI, CPI, DCPI and TDNI in the three groups of cows. Ether extract digestibility was higher (P